2017
DOI: 10.5812/mejrh.44558
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Achievement Motivation, and Academic Progress of Students with Learning Disabilities: A Comparison with Typical Students

Abstract: Introduction: Many factors including self-efficacy and achievement motivation can affect children's academic progress. Studies have shown that socioeconomic status can affect people's life, education, and vocation. However, not many studies looked at the relations between the intrinsic factors and socioeconomic status, and between these 2 categories and students' academic progress in children with learning disabilities. Thus, the present study aimed at examining self-efficacy, achievement motivation, and acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…All Rights Reserved. (Seyed, Salmani, Motahari Nezhad, & Noruzi, 2017). However, a more distinctive report by Prasad (2017) about the adjustment of PWD using the CAS test, the same measure utilized in the present study, found that they struggle with anxiety, depression, suicidal ideation, and career and interpersonal problems.…”
Section: College Adjustment Of Pwdmentioning
confidence: 43%
“…All Rights Reserved. (Seyed, Salmani, Motahari Nezhad, & Noruzi, 2017). However, a more distinctive report by Prasad (2017) about the adjustment of PWD using the CAS test, the same measure utilized in the present study, found that they struggle with anxiety, depression, suicidal ideation, and career and interpersonal problems.…”
Section: College Adjustment Of Pwdmentioning
confidence: 43%
“…In general, social support and self-efficacy can be considered as important factors for stress resistance (Everly and Lating, 2019). These factors are less developed in adults with MID (Abbaszadeh and Sardoie, 2016;Seyed et al, 2017). The relatively high impact of daily stressors, such as taxing social interactions, may also be explained by the lack of control over both minor daily and major life decisions (Hartley and MacLean, 2009b;Dulin et al, 2013;Scott and Havercamp, 2014).…”
Section: Experience Of Stress In People With Midmentioning
confidence: 99%
“…Comparative studies, both national and international, have reported below benchmark achievements among Ghanaian basic school students in mathematics (Anamuah- Mensah & Mereku, 2005;Anamuah-Mensah, Mereku, & Asabere-Ameyaw, 2008;Butakor, Ampadu, & Cole, 2017;Gunhan, 2014;Mullis, Martin, & Foy, 2008). Studies have shown that academic achievement has several determinant extending from socio-economic status (Barakzai & Fraser, 2005), learning disabilities (Seyed, Salmani, Nezhad, & Noruzi, 2017), students interest (Alfa & Karim, 2016), teaching methods (Asante & Mereku, 2012), school entry modalities (Cameson & Wilson, 2011), and to Gender (Cunningham, 2016). Studies are fast refuting many past beliefs that males perform better than females (Abubakar, 2010;Erdoğan, Baloğlu, & Kesici, 2011) and prompting more investigations.…”
Section: Problem Statementmentioning
confidence: 99%